(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the severity of different atherosclerotic lesions in relation to occupational physical activity in our population. Study design: Prospective descriptive observational study. Place and duration of study: Mortuary of King Edward Medical University Lahore and Department of Pathology Allama Iqbal Medical College Lahore. The duration of study was completed in one and a half year. Materials and Methods: A total of 130 human autopsies were carried out at random. The age range was between 8 and 85 years. Heart, aorta coronary arteries and renal arteries were collected from dead bodies. One to four areas of tissue were taken from aorta and each arteries in all cases. Sections were prepared from paraffin blocks. These were stained with Haematoxylin and Eosin stain. Special stain were also performed to differentiate all the components of atherosclerotic lesions. Results: The fatty streaks were present in a predominant number of cases in Grade-II and Grade-III than in Grade-I physically activity cases. The fibrolipid plaques, complicated and classified lesions were seen predominantly in Grade-I than in Grade-II and Grade-III physically active cases on percentage basis. Conclusion: In this study the severity of different atherosclerotic lesions is noted in Grade-I, Grade-II and Grade-III physically active subjects according to their occupational activities. This basic data gives indication and guideline for prevention and control of atherosclerotic process by increasing physical activity in life style of our population.